1999
DOI: 10.1093/nar/27.11.2304
|View full text |Cite
|
Sign up to set email alerts
|

The role of components of recombination signal sequences in immunoglobulin gene segment usage: a V81x model

Abstract: It has long been appreciated that some immunoglobulin (and T-cell receptor) gene segments are used much more frequently than others. The VHsegment V81x is a particularly striking case of overusage. Its usage varies with the stage of B-cell development and with the strain of mice, but it is always high in B cell progenitors. We have found that the coding sequence and the recombination signal sequences (RSS) are identical in five mouse strains, including CAST/Ei, a strain derived from the species Mus castaneus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…It has been shown that 81X rearranges 7-to 30-fold more frequently than the V H J558 gene in a competition substrate (22,23). However, the V H J558 genes have very poor RSS, and the nonamer is so different from the consensus that it is not clear whether they also have a shortened, less functional, 22-bp spacer (see Fig.…”
Section: Analysis Of the Role Of The Rss In The Nonrandom V H Gene Usementioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that 81X rearranges 7-to 30-fold more frequently than the V H J558 gene in a competition substrate (22,23). However, the V H J558 genes have very poor RSS, and the nonamer is so different from the consensus that it is not clear whether they also have a shortened, less functional, 22-bp spacer (see Fig.…”
Section: Analysis Of the Role Of The Rss In The Nonrandom V H Gene Usementioning
confidence: 99%
“…It has been proposed that the reason that 81X rearranges so often is due to its RSS (23). Using miniloci recombination substrates transiently transfected into pre-B cells, the relative frequency of rearrangement of 81X vs V H J558 genes was determined, and 81X rearranged ϳ15 times more often than V H J558 (22,23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3). Several groups have emphasized that the level at which certain B cell receptor specificities occur in vivo might be dictated to some extent by family-specific RSS characteristics (24)(25)(26). RSS replacement during evolution means that under some circumstances, V genes with advantageous binding properties may evolve to have an appropriate level of representation in the immune repertoire through shuffling of RSS elements.…”
Section: Is Rss Type H3 the Most Efficient For V(d)j Recombination?mentioning
confidence: 99%
“…Some of the elements regulating V-to-D joining are different from those regulating D-to-J joining (45)(46)(47). We can think of two possibilities as to why V H replacement occurs during thymic development in the QM strain but is not detectable in unmanipulated strains.…”
Section: Discussionmentioning
confidence: 99%